CCL17 and CCL22 chemokines are upregulated in human obesity and play a role in vascular dysfunction - Hueso, Luisa; Marques, Patrice; Morant, Brenda; Gonzalez-Navarro, Herminia; Ortega, Joaquin; Real, José T.; Sanz, María J; Piqueras, Laura (Frontiers in Endocrinology, 2023)
Background/Aims: Chemokines are known to play critical roles mediating inflammation in many pathophysiological processes. The aim of this study was to investigate the role of chemokine receptor CCR4 and its ligands CCL17 and CCL22 in human morbid obesity. Methods: Circulating levels of CCL17 and CCL22 were measured in 60 morbidly obese patients (mean age, 45±1 years; body mass index/BMI, 44±1 kg/m2) who had undergone bariatric bypass surgery, and 20 control subjects. Paired subcutaneous (SCAT) and visceral adipose tissue (VCAT) from patients were analysed to measure expression of CCR4 and its ligands by RT-PCR, western blot and immunohistochemical analysis. The effects of CCR4 neutralization ex vivo on leukocyte-endothelial cells were also evaluated. Results: Compared with controls, morbidly obese patients presented higher circulating levels of CCL17 (p=0.029) and CCL22 (p<0.001) and this increase was positively correlated with BMI (p=0.013 and p=0.0016), and HOMA-IR Index (p=0.042 and p< 0.001). Upregulation of CCR4, CCL17 and CCL22 expression was detected in VCAT in comparison with SCAT (p<0.05). Using the parallel-plate flow chamber model, blockade of endothelial CCR4 function with the neutralizing antibody anti-CCR4 in morbidly obese patients significantly reduced leucocyte adhesiveness to dysfunctional endothelium, a key event in atherogenesis. Additionally, CCL17 and CCL22 increased activation of the ERK1/2 mitogen-activated protein kinase signalling pathway in human aortic endothelial cells, which was significantly reduced by CCR4 inhibition (p=0.016 and p<0.05). Conclusions: Based on these findings, pharmacological modulation of the CCR4 axis could represent a new therapeutic approach to prevent adipose tissue dysfunction in obesity.